A Novel Sensory Nerve Conduction Study Technique to Evaluate the Sural Nerve From the Forefoot to the Knee. Issue 2 (April 2015) - Zuo, Kevin J.; Lee, Robyn; Clarke, Nicole A.; Dong, Anson; Chan, K. Ming
Abstract : Purpose: Length-dependent polyneuropathy is common. Current electrophysiological methods cannot assess sensory nerve function proximal to the distal calf, limiting their utility in the quantification of severity of length-dependent polyneuropathy. Methods: The authors developed a novel electrophysiological approach for distal to proximal assessment of the sural nerve between the forefoot and the knee and tested it on 63 healthy young, middle-aged, and old adults. Results: It was feasible to elicit sensory nerve action potentials in the forefoot, ankle, and knee segments of the sural nerve in all subjects. Intraobserver ( r = 0.87) and interobserver ( r = 0.87) reliability were high. Sensory nerve action potential amplitudes were greatest at the ankle, followed by the knee and forefoot. Sensory nerve action potential amplitudes in the forefoot and ankle were significantly smaller in the old age group (>60 years) compared with the young age group (20–39 years) ( P < 0.05). In contrast, neither age nor gender had a significant impact on sensory nerve action potential conduction velocities. Conclusions: The authors demonstrated that reliable electrophysiological recordings of the sural nerve as proximal as the knee are feasible. This novel technique may be useful in patients with length-dependent polyneuropathy to monitor progression and to evaluate treatment response.